PENDEKATAN EDUTAINMENT DALAM PEMBELAJARAN PAI DI SMPN 24 GRESIK - Rosa Nia Wahyuningtyas; Ali Ahmad Yenuri (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2024)
This study aims to describe the implementation of edutainment learning in Islamic Religious Education (PAI) and to analyze its impact on the learning motivation of students at SMPN 24 Gresik. This research employed a qualitative case study design. Data were collected through moderate participatory observation, in-depth interviews, and documentation. The informants consisted of Islamic Religious Education teachers, eighth-grade students, and school staff related to the learning process. Data analysis was conducted through data reduction, data display, and conclusion drawing, while validity was ensured through source and method triangulation. The results show that edutainment learning was implemented through planning, implementation, and evaluation. Teachers prepared learning modules, selected interactive methods, combined explanation with question-and-answer activities, quizzes, educational games, group discussions, and Islamic-based digital media, and used written tests, practice-based assessment, and feedback. The approach had a positive impact on students' learning motivation, reflected in increased enthusiasm, participation, confidence, activeness, and interest in learning PAI. Therefore, edutainment can be used as an alternative strategy for strengthening PAI learning that is relevant to students.